Physical Activity Training Education for the Elderly at Nursing Homes - Acep Ranal; Husniyah Husniyah; Yulia Fienti; Sindi Andika Putri; Farinas Lenin; Musrika Musrika; Dewi Diana; Derr Xin (Yayasan Adra Karima Hubbi, 2023)
Background. The gerontological nursing stage is one part of the clinical practice of the nursing profession that must be completed by students. As a form of achieving learning goals, we provide counseling about the importance of physical activity training for the elderly. The process that occurs in general in the elderly progressively which results in changes that cause organ dysfunction and failure of an organ or a particular body system is called aging. Aging (getting old) is the process of slowly losing the ability of a network with the aim of maintaining its normal function and repairing itself so that the defense against infection is reduced and the damage experienced can be repaired. Some of the health problems experienced by the elderly include hypertension, sensory disturbances, tremors, diabetes mellitus, and dementia. Various types of interventions can be given to increase the knowledge and ability of the elderly to be able to maintain their health, therefore students provide education on the importance of physical activity training for the elderly. Purpose. This activity aims to: increase the knowledge of the elderly and self-awareness to carry out routine health checks. Method. This activity involved 10 who can take part in educational activities on the importance of physical activity training and checking blood pressure and muscle strength in the elderly. Students use the method; pre and post conference, namely before carrying out activities, students measure knowledge, blood pressure and muscle strength of the elderly, then intervention is carried out by educating the importance of physical activity training. Results. Elderly who take part in the activity experience an increase in blood pressure which is still within normal limits and an increase in muscle strength. Conclusion. There is a significant difference regarding knowledge in applying activity therapy between the pre test and post test, this shows the ability and increase in the elderly in realizing the importance of physical activity training.